Enhanced photoluminescence due to Bi3+ → Eu3+ energy transfer and re-precipitation of RE doped homogeneous sized Y2O3 nanophosphors. (November 2016) - Jadhav, Abhijit P.; Thi Dinh, Thuy Duong; Khan, Sovann; Lee, Seung Yong; Park, Jong-Ku; Park, Sung Wook; Oh, Ju Hyun; Moon, Byung Kee; Jang, Kiwan; Yi, Soung Soo; Kim, Jung Hwan; Cho, So-Hye; et al.
Graphical abstract: Highlights: Successful re-precipitation of supernatant solution to obtain phase pure nanophosphors. Fine tuning emission wavelength by adding dopant during re-precipitation reaction. Efficient luminescence enhancement with Bi 3+ → Eu 3+ energy transfer. Abstract: Precipitation and re-precipitation of metal ions has been carried out from original and supernatant solution producing Bi 3+ – Eu 3+ doped Y2 O3 :Eu 3+ and Eu 3+ /Tb 3+ doped Y2 O3, respectively. Shorter reaction time is unable to consume all metal ions present in the solution which can be utilized through re-precipitation process. The doping of Bi 3+ – Eu 3+ in Y2 O3 helps to absorb maximum UV light. The activation of Y2 O3 matrix by Bi 3+ and Eu 3+ ions, together and separately, were studied considering the excitation energy transfer to the luminescence centers. The successful replacement of Y 3+ by RE 3+ ions can help for fine tuning of emission wavelength. Re-precipitation of supernatant solution by adding terbium precursor can successively produce uniform sized Tb 3+ doped Y2 O3 :Eu 3+ . The re-precipitation of the supernatant solution ensures maximum consumption of metal ions for higher product yield and possible fine tuning of emission wavelengths.